Analysis of E-Commerce Adoption Factors by Micro, Small, and Medium Enterprise, and Its Effect on Operating Revenue - Arline Prameswari Effendi; Bambang Subroto (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This research aims to examine the effect of organizational readiness, external pressure, and perceived benefits on micro, small, and medium enterprises’ e-commerce adoption, and to examine the effect of e-commerce adoption by MSMEs on operating revenue. The sample of this study is MSME owners and managers in Malang city. Data were collected by survey method using convenience sampling technique. The relationship between variables in this study were analyzed using Partial Least Square (PLS) with SmartPLS application. The results of this study indicate that external pressure and perceived benefits influence MSMEs’ e-commerce adoption, while organizational readiness does not influence MSMEs’ e-commerce adoption. In addition, e-commerce adoption increases MSME’s operating revenue.